2006
DOI: 10.1248/bpb.29.1597
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalin Induces Apoptosis through Regulation of Bax and Bcl-2 Expressions in Human DU145 and LNCaP Prostate Cancer Cells

Abstract: Amygdalin (vitamin B 17 ; previously called laetrile) is one of many nitrilosides, which are natural cyanide-containing substances abundant in the seeds of prunasin family, plant such as apricots, almonds, peaches, apples, and other rosaceous plants. Among the prunasins, Armeniacae semen has been used for the treatment of asthma, bronchitis, emphysema, leprosy, colorectal cancer, leucoderma, and pain. [1][2][3] Amygdalin is composed of two molecules of glucose, one of benzaldehyde, which induces an analgesic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
120
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(127 citation statements)
references
References 34 publications
4
120
0
3
Order By: Relevance
“…Amygdalin, sometimes known as laetrile or vitamin B17, is one of the natural cyanogenic diglucoside existing in the fruits and nuts, such as cherries, apricots kernels, apples and almonds (Holzbecher et al 1984;Santos Pimenta et al 2014). It has been previously reported that amygdalin treatment in human cancer cells exerts a potential cytotoxic and anti-cancer effects by inducing apoptotic cell death (Syrigos et al 1998;Chang et al 2006;Chen et al 2013), arrest cell cycle through downregulation of cell cycle-related genes (Park et al 2005;Makarević et al 2014a) and blocking metastasis that can lead to the spread of cancer to other tissues (Makarević et al 2014b). Primarily, cancer has been treated by using conventional therapies; however, amygdalin is also used as an alternative medicine and was found one of the most useful and effective alternative in cancer therapy (Milazzo et al 2007;Sauer et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Amygdalin, sometimes known as laetrile or vitamin B17, is one of the natural cyanogenic diglucoside existing in the fruits and nuts, such as cherries, apricots kernels, apples and almonds (Holzbecher et al 1984;Santos Pimenta et al 2014). It has been previously reported that amygdalin treatment in human cancer cells exerts a potential cytotoxic and anti-cancer effects by inducing apoptotic cell death (Syrigos et al 1998;Chang et al 2006;Chen et al 2013), arrest cell cycle through downregulation of cell cycle-related genes (Park et al 2005;Makarević et al 2014a) and blocking metastasis that can lead to the spread of cancer to other tissues (Makarević et al 2014b). Primarily, cancer has been treated by using conventional therapies; however, amygdalin is also used as an alternative medicine and was found one of the most useful and effective alternative in cancer therapy (Milazzo et al 2007;Sauer et al 2015).…”
mentioning
confidence: 99%
“…Primarily, cancer has been treated by using conventional therapies; however, amygdalin is also used as an alternative medicine and was found one of the most useful and effective alternative in cancer therapy (Milazzo et al 2007;Sauer et al 2015). The cytotoxic effects of amygdalin against cancer cells are related with the release of hydrogen cyanide (HCN), which is an antitumor compound, decomposing carcinogenic substances in the body, inhibiting cancer growth and blocking nutrient source of tumor cells (Syrigos et al 1998;Chang et al 2006). The release of HCN from amygdalin glycoside is also related with activity of β-glucosidase enzyme that catalyzes the hydrolysis of covalent bonds linking two glucose or glucose-substituted molecules (Syrigos et al 1998).…”
mentioning
confidence: 99%
“…Amigdalinin insan prostat kanser hücrelerinde (DU145 ve LNCap) programlanmış hücre ölümünü (apoptoz) teşvik ettiği saptanmıştır [56]. Park ve ark.…”
Section: Tedavi Edici Etkisiunclassified
“…Amygdalin, can be used for an effective prevention and treatment of human cancer (Gomez et al, 1998). However, the Food and Drug Administration (FDA) has not approved amygdalin as a cancer treatment owing to insufficient clinical evidence of its efficacy and potential toxicity (Chang et al, 2006;Kwon et al, 2010). The seed oil has been used to treat tumors, ulcers (Rieger, 2006) well as in cosmetics and as a pharmaceutical agent (laxative and expectorant).…”
Section: Introductionmentioning
confidence: 99%